A Comprehensive Definition and Typology of Anglicisms in Present-day Spanish - Núñez Nogueroles, Eugenia Esperanza (Epos : Revista de filología, 2019)
The aim of the present piece of research is twofold. On the one hand, it attempts to provide a clear and accurate definition of the term Anglicism. On the other hand, it delves deeply into the different loanword classifications that have been expounded so far in order to take them as the basis for elaborating an inclusive, comprehensive and consistent typology of Anglicisms as they are used in present-day Spanish. This taxonomy improves the existing ones in that it covers true as well as false Anglicisms and, moreover, it adds two new categories of pseudo-Anglicisms. RESUMEN El presente trabajo de investigación se propone, por un lado, proporcionar una definición clara y precisa del término anglicismo y, por otro, ahondar en las diferentes clasificaciones de préstamos que se han publicado hasta el momento, con el objetivo de tomarlas como base para la elaboración de una tipología sólida, compleja y completa de los anglicismos empleados en el español actual. Esta taxonomía supondrá un avance con respecto a las ya existentes, dado que incluirá tanto los anglicismos auténticos como los falsos y, además, añadirá dos nuevas categorías al ámbito de los pseudo-anglicismos.